The Utilization of Prompting Based-Meta AI in Production of Qur'an Essay Content on NgajiTafsir.com Website; Some Opportunities and Challenges - Ma'arif, Cholid Zwei (Library of Sultan Agung Islamic University, 2025)
Advances in artificial intelligence technology are increasingly reaching a wider target user. Most recently, the emergence of Meta AI, a sophisticated communication feature embedded in the Whatsapp social media platform. In this case, the NgajiTafsir.com website management community seeks to innovate by utilizing the Meta AI application prompting in creating Islamic content based on the interpretation of the Qur'an. This research aims to examine the opportunities and challenges of applying AI theoretically and practically managing the creation of Qur'anic interpretation website content based on Meta AI prompting on the Whatsapp application. The method used is a mix-method with experimental data collection and data analysis based on literature studies. The result of this finding is that the Whatsapp-based Meta AI prompter made important mistakes in quoting verses of the Qur'an quoted in 3 out of 10 essays as well as citing the identity and reference details of the book of tafsir in 4 of the book of tafsir. So that there are opportunities to use it: a) as an effective and efficient media for accessing information, 2) interactive education provides a new learning experience for users, 3) personalization of interaction with users in a natural and intuitive way. Meanwhile, the challenges are the risk of errors that require sophisticated human resources, the basic character of the Whatsapp application which is the home of Meta AI, and the monotonous and simple programming language. So researchers argue that using of Whatsapp-based Meta AI prompting is vulnerable to be interacted with scientifically and in-depth.